Star Shaped Poly(ethylene glycols) Yield Biocompatible Gene Delivery Systems - Iemsam-Arng, Jayanant; Kong, Xiao; G. Schatzlein, Andreas; F. Uchegbu, Ijeoma (Pharmaceutical Nanotechnology, 2014)
Cationic gene delivery molecules are relatively cytotoxic [50% cell survival concentrations (IC50) < 0.05 mg mL-1], limiting their use clinically. We hypothesise that a low molecular weight polymer with reduced amine content would yield biocompatible gene therapy nanoparticles with DNA. We synthesised and characterised an amine terminated poly(ethylene glycol) – (PEG) based polymer - tetra-O,O,O,O-[poly(ethyleneglycol-O-2- ethyleneimine)-graft-N-(2-ethylamine)-]-pentaerythritol (4-arm-PEG-ethylamine - 4APEA) and subjected 4APEA to physicochemical and biological testing. 4APEA was relatively non-toxic against the A431 cell line (IC50 of 4.76 ± 0.27 mg mL-1), formed 200 nm positively charged nanoparticles with DNA and transfected the A431 cell line with a similar efficacy to the less biocompatible poly(ethylenimine) (PEI, IC50 = 0.002 mg mL-1). On intravenous injection of 4APEA – DNA nanoparticles, significantly more DNA was found in the lungs and liver when compared to the injection of DNA alone. When 4APEA, 4APEA -TNF-alpha DNA nanoparticles and TNF-alpha DNA alone were intravenously injected to MiaPaCa tumour bearing mice, only the 4APEA - TNF-alpha DNA nanoparticles were tumouricidal, with tumour volumes significantly different from untreated controls. A new PEG derivative 4APEA is 1000 time less toxic than PEI in the A431 cell line, has comparable cell transfection capability to PEI in this cell line and produces tumouricidal nanoparticles when complexed with TNF-alpha.
Keywords: poly(ethylene glycol)